Seizures in Primary Antiphospholipid Syndrome: The Relevance of Smoking to Stroke - Jozélio Freire de Carvalho; Sandra Gofinet Pasoto; Simone Appenzeller (Clinical and Developmental Immunology)
Objectives. To evaluate the frequency of seizures in primary antiphospholipid syndrome (PAPS) and their possible clinical and laboratory associations. Methods. Eighty-eight PAPS patients (Sydney’s criteria) were analyzed by a standard interview, physical examination and review of medical charts. Risk factors for seizures, clinical manifestations, associated comorbidities, and antiphospholipid antibodies were evaluated. Results. Nine (10.2%) patients with seizures were identified, 77.8% had convulsions onset after PAPS diagnosis. Mean age, gender, and race were comparable in groups with or without seizures. Interestingly, a higher frequency of current smoking (44.4 versus 10.1%, 𝑃=0.019) was observed in the first group. Stroke, Sneddon’s syndrome, and livedo reticularis were more frequent in PAPS patients with seizures than those without seizures, although not statistically significant (𝑃>0.05). Comparison between patients with seizures onset after PAPS diagnosis (𝑛=7) and those without convulsions (𝑛=79) demonstrated a higher frequency of current smoking (42.9 versus 10%, 𝑃=0.042) and stroke in the first group (71.4 versus 30.4%, 𝑃=0.041). Regression analysis confirmed that smoking (𝑃=0.030) and stroke (𝑃=0.042) were independently associated to seizures. Conclusion. About 10.2% of PAPS patients had convulsions, predominantly after PAPS diagnosis, and seizures were associated to current smoking and stroke.